PELATIHAN PENYUSUNAN MODEL SPORT EDUCATION SEBAGAI UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN PENDIDIKAN JASMANI DI SEKOLAH - Sismadiyanto, Sismadiyanto (Universitas Negeri Yogyakarta, 2011)
This training aims at giving preview in the arrangement of swimming teaching model based on religious moral values for students of FIK UNY. There are two approaches for activities method. First is theoretical approach which consists of material presentation, discussion, and question answer. Se- cond one is practical approach which consists of mastering the swimming basic technique, class management based on religious moral values, water games, etc. Each of approaches then was evaluated using swimming teaching program based on religious moral values. The material presentation focuses on: theo- retical and practical material about swimming basic skill, swimming rules, basic safety water, and swimming teaching model based on religious moral values. The indication of training successfulness could be seen from the high motivation of participants in following it and also from the new science and skill about swimming learning model based on religious moral values that was gotten. The program of people service was going well and followed by 31 of participants. Based on result discussion that was presented then there are some high light points: (1) There are lots of students voices that hoping a special class in swimming subject which separates male and female students, (2) They also want to use swimsuit that can close over the body, (3) there is a tension from female students who wear veil then she leave out it because of swimming rule about cloth manner in swimming class, (4) time for swimming class is just same with public visitors who also use same facilities of pool so then it could be like a public show for them, (5) It should be a female teacher for female students and a male teacher for males